Analysis of Value Stream Mapping (VSM) in the Application of Lean Manufacturing to Minimize Waste at PT. Karya Indah Medika - Fatinnisa, Ghina Aldra; Saifuddin, Joumil Aidil (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
Achievements to minimize waste can be done by adopting a Lean manufacturing approach. Lean manufacturing is a concept that can design production processes to be better, faster, and cheaper with minimal space, small inventory, small labor hours, and avoid waste. This research takes the case study of PT Karya Indah Medika which is a company engaged in manufacturing to produce medical devices, medical device service services, and medical device installation. In the company there is still waste, especially in unnecessary movements and product defects. This study aims to identify waste that occurs in the company and provide recommendations for improvements in order to minimize waste and obtain optimal production time. Value stream mapping is used to describe all processes in the company. The results showed that the initial production time of 17 hours 18 minutes could be reduced to 1 hour 55 minutes. Based on the Failure Mode and Effect Analysis (FMEA) it is known that the root cause of the problem in the highest waste is workers in a hurry so they are not thorough in working with a Risk Priority Number (RPN) score of 294, lack of materials needed for production, placement of tools that are not in accordance with production needs and a warehouse area that is less extensive by 216.